QT AS A MEANS OF CROSS-PLATFORM DEVELOPMENT - Lavrik, A.B.; Kutetsky, Д.В. (Journal of Information Technologies in Education (ITE), 2010)
This article observes abilities of cross-platform software development kit Qt, and compares them with abilities of Java libraries.